Telling Friend from Foe: Listeners Are Unable to Identify In-Group and Out-Group Members from Heard Laughter - Ritter, Marie; Sauter, Disa A. (Frontiers in Psychology, 2017)
Group membership is important for how we perceive others, but although perceivers can accurately infer group membership from facial expressions and spoken language, it is not clear whether listeners can identify in- and out-group members from nonverbal vocalizations. In the current study, we examined perceivers’ ability to identify group membership from nonverbal vocalizations of laughter, testing the following predictions: (1) listeners can distinguish between laughter from different nationalities and (2) between laughter from their in-group, a close out-group, and a distant out-group, and (3) greater exposure to laughter from members of other cultural groups is associated with better performance. Listeners (n=814) took part in an online forced-choice classification task in which they were asked to judge the origin of 24 laughter segments. The responses were analysed using frequentist and Bayesian statistical analyses. Both kinds of analyses showed that listeners were unable to accurately identify group identity from laughter. Furthermore, exposure did not affect performance. These results provide a strong and clear demonstration that group identity cannot be inferred from laughter.